NIETZSCHEAN WILL TO POWER AND THE POLITICS OF PERSONALITIES IN PUBLIC DIPLOMACY - ANAKWUE, Nicholas (Socialscientia: Journal of Social Sciences and Humanities, 2018)
The task of understanding and perfecting international and diplomatic relations is becoming more crucial, given the frequency of political disputes and intimidation via public diplomacy. At the root of this trend is the dominance of political personalities in international relations, dictating the direction and progress of conflict control on the international scene. With increasing technological, biological, chemical and nuclear weaponry, ignorance of and any mistaken decision on the diplomatic terrain can come at a huge cost of war and anarchy. At the heart of personalities and human relations, however, Nietzsche argues, is the will to power, that singular striving of each individual to assert his individuality and uniqueness, most times, to the detriment of collective interest. The objective of this paper is to expose what Nietzsche means by will to power in order to allow us have a handle on its influence on politics and social relations. The research question, therefore, addresses the relationship between will to power and the nature of political relationships in public diplomacy. The paper will achieve this by an expository and analytical method of research. The paper finds out that it is apposite that we gain control over the tendency for political persons to exploit public diplomacy to dastardly ends. This is to prevent a consequent descent into anarchy, one that Hobbes describes in grotesque clarity as the war of everyone against everyone, with life being “nasty, brutish and short.”